2015
DOI: 10.1063/1.4922810
|View full text |Cite
|
Sign up to set email alerts
|

Determination of deep-level defects in Cu2ZnSn(S,Se)4 thin-films using photocapacitance method

Abstract: Deep-level defects were investigated in Cu2ZnSn(S,Se)4 and Cu2ZnSnS4 thin-films using transient photocapacitance (TPC) spectroscopy. A deep-defect, OH1 centered around 1.0 eV above the valance-band (EV) of Cu2ZnSnS4 has been identified at room temperature (RT). However, OH1-defect could be identified in Cu2ZnSn(S,Se)4 at low temperature only. Absence of OH1-defect in Cu2ZnSn(S,Se)4 at RT explains its better performance comparing to Cu2ZnSnS4 solar-cell. A comparative study of the TPC spectra of the Cu(In,Ga)Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Therefore, alternative but more demanding methods have been used so far, such as quantum effi ciency (QE) analysis, photoluminescence, or photocapacitance. [ 63,75 ] The red bars show the acceptor levels and the blue bars show the donor levels, with the initial and fi nal charge states labeled in parentheses. Reproduced with permission.…”
Section: Band Tailing and Its Potential Originmentioning
confidence: 99%
“…Therefore, alternative but more demanding methods have been used so far, such as quantum effi ciency (QE) analysis, photoluminescence, or photocapacitance. [ 63,75 ] The red bars show the acceptor levels and the blue bars show the donor levels, with the initial and fi nal charge states labeled in parentheses. Reproduced with permission.…”
Section: Band Tailing and Its Potential Originmentioning
confidence: 99%
“…TPC [84] highest solar cell efficiencies have been achieved at low Cu and high Zn compositions which should decrease the formation of Cu Zn and promote the formation V Cu . The Zn-rich and Cu-poor compositions of CZTS and CZTSe should also help to avoid the formation of detrimental Sn-related deep defects such as Cu Sn , Sn Cu and Sn Zn and associated defect complexes.…”
Section: Intrinsic Defects In Kesteritesmentioning
confidence: 99%
“…According to the reported information, such as the density and the carrier capture cross-section of the defects, measured by DLTS, here we can estimate the shortest carrier lifetime of CZTSSe by Equation (5). The calculated carrier lifetimes τ c are listed in Table 2 [89,90,101,[105][106][107][108][109][110][111][112]. Unexpectedly, the τ c values derived from the DLTS are in the order of microsecond or even millisecond, which is several orders of magnitude larger than the measured result (τ m ).…”
Section: Experimental Identification Of Defectsmentioning
confidence: 82%
“…Based on the above discussions, it can be found that the CZTSSe material indeed possesses more serious atomic disorder and band tail states compared with other semiconductors. A previous summary of the Urbach energy (E U ) of the CZTSSe and other materials clearly shows this fact [41,[88][89][90]. E U is also a featured parameter reflecting the band tail states.…”
Section: Cu/zn Disorder: Influencementioning
confidence: 88%